Control of Improved Hybrid Power Line Conditioner - Zhuk, Oleksandr; Zhuk, Dmytro; Kryvoruchko, Dmytro; D’yakonov, Oleksiy (My University, 2018)
Features of static and dynamic modes of the improved hybrid adjustable power line conditioner (APLC) in the autonomous electric power system (EPS) with powerful semiconductor converters (SC) are considered. The conditions for full compensation of the reactive power (RP) of the load are determined and the principles of constructing the structure of the corresponding automatic control system (ACS) of the APLC are proposed. The MATLAB-model of the system was created and investigated to optimize the regulator parameters to achieve the quality of transients and provide conditions for electromagnetic compatibility (EMC).
Control of Improved Hybrid Power Line Conditioner / O. Zhuk, D. Zhuk, D. Kryvoruchko, O. D’yakonov // 38th Intern. Conf. on Electronics and Nanotechnology (ELNANO). – Kyiv, 2018. – P. 605–610.
Keywords: adjustable power line conditioner (APLC); inactive components of the total power; reactive power (RP); power quality (PQ); voltage and current harmonic distortion factors; pulse-width modulation (PWM); controlled reactor compensator (CRC); synchronous generator (SG)